Comparative Transcriptome Analysis Reveals Effects of Exogenous Hematin on Anthocyanin Biosynthesis during Strawberry Fruit Ripening - Yi Li; Huayin Li; Fengde Wang; Jingjuan Li; Yihui Zhang; Liangju Wang; Jianwei Gao (International Journal of Genomics)
Anthocyanin in strawberries has a positive effect on fruit coloration. In this study, the role of exogenous hematin on anthocyanin biosynthesis was investigated. Our result showed that the white stage of strawberries treated with exogenous hematin had higher anthocyanin content, compared to the control group. Among all treatments, 5 μM of hematin was the optimal condition to promote color development. In order to explore the molecular mechanism of fruit coloring regulated by hematin, transcriptomes in the hematin- and non-hematin-treated fruit were analyzed. A large number of differentially expressed genes (DEGs) were identified in regulating anthocyanin synthesis, including the DEGs involved in anthocyanin biosynthesis, hormone signaling transduction, phytochrome signaling, starch and sucrose degradation, and transcriptional pathways. These regulatory networks may play an important role in regulating the color process of strawberries treated with hematin. In summary, exogenous hematin could promote fruit coloring by increasing anthocyanin content in the white stage of strawberries. Furthermore, transcriptome analysis suggests that hematin-promoted fruit coloring occurs through multiple related metabolic pathways, which provides valuable information for regulating fruit color via anthocyanin biosynthesis in strawberries.